The ambivalent impact of COVID-19 on churches: The case of Nigeria - Asadu, George C. (HTS teologiese studies, 2022)
The outbreak of the coronavirus disease 2019 (COVID-19) since November 2019 has increased the challenges of human existence. Before the pandemic there were the issues of insecurity, religious and racial bigotry, climate change, poverty and so forth, which to a large extent have affected humanity negatively. The lockdown, which was introduced as a measure to curb the spread of the virus, exacerbated the anguish of the already tense world. Suddenly, the government proscribed gatherings of people in large numbers, thereby suspending economic, cultural and social activities. The continued increase of the COVID-19 cases necessitated the shutdown of worship centres. It was the first time churches would be shut down in Nigeria. The incident provoked concerns and interests in public discourse and intellectual circles. Therefore, this study examines the effects of COVID-19 on churches, using a historical approach and basically depending on secondary sources from available literature and Internet sources of information. The findings show that it was the lockdown that affected the churches most, rather than the virus. The suspension of corporate worship, sacramental rites, evangelistic outreaches and pastoral visits posed a significant challenge to the churches, affecting members’ psychology and leading to a decline in church revenue and an increase in charity services. The study therefore recommends that churches be digitalised and house fellowships be revitalised.Contribution: Regardless of the impact the lockdown had on the churches, it conscientised them about the proper use of their personnel and material resources. Nowadays, churches do ministry differently, adapting to changing circumstances and harnessing divergent Christian concepts of faith and divine healing by combining science and faith in health-related theologies.